2008
DOI: 10.17221/405-pse
|View full text |Cite
|
Sign up to set email alerts
|

Effects of some plant growth regulators on stem anatomy of radish seedlings grown under saline (NaCl) conditions

Abstract: In this work, effects of gibberellic acid, 2-chloroethylphosphonic acid (ethephon), triacontanol, 24-epibrassinolide and polyamine (cadaverine, putrescine, spermidine, spermine) pretreatments on the stem anatomy of radish seedlings grown under saline conditions were studied. Salt stress decreased the stem diameter, epidermis cell size, cortex zone thickness, vascular bundle width, cambium thickness, xylem width, trachea diameter and phloem width in the seedlings non-pretreated with the growth regulators, in co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
9
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(10 citation statements)
references
References 26 publications
1
9
0
Order By: Relevance
“…From all characters of physiology, morphology and anatomy for the C. arabica from three different habitats, this study indicates that, the C. arabica which grows in site one (high salinity) is characterized by increase in the leaf size, lobe number, thickening of epidermis, area of vascular bundles, chlorophyll a, b, cartenoid and prolein as adaptive characters for salinity stress; this agrees with the view of (Vijayan et al, 2008, Çavuşoğlu et al, 2008, Wu et al, 2010, Chookhampaeng, 2011, Ahmad et al, 2012, Kishor and Sreenivasulu, 2014). This study supports the use of C. arabica and these characters are used as an indicator of the salinity of the soil.…”
Section: Resultssupporting
confidence: 86%
See 1 more Smart Citation
“…From all characters of physiology, morphology and anatomy for the C. arabica from three different habitats, this study indicates that, the C. arabica which grows in site one (high salinity) is characterized by increase in the leaf size, lobe number, thickening of epidermis, area of vascular bundles, chlorophyll a, b, cartenoid and prolein as adaptive characters for salinity stress; this agrees with the view of (Vijayan et al, 2008, Çavuşoğlu et al, 2008, Wu et al, 2010, Chookhampaeng, 2011, Ahmad et al, 2012, Kishor and Sreenivasulu, 2014). This study supports the use of C. arabica and these characters are used as an indicator of the salinity of the soil.…”
Section: Resultssupporting
confidence: 86%
“…These changes are physiological, morphological and anatomical (Shannon, 1997, Isla et al, 1998). It has been revealed from many studies that high salinity mostly causes anatomical alterations such as reduction of stomata number, leaf thickness, distance between vascular bundles and epidermis cell number (Shennan et al, 1987, Hwang and Chen, 1995, Kiliç et al, 2007, Çavuşoğlu et al, 2007, Vijayan et al, 2008, Çavuşoğlu et al, 2008). Other structural changes that occurred in salt stressed plants such as inhibition of differentiation, diameter and number of xylem vessels have also been recorded.…”
Section: Introductionmentioning
confidence: 99%
“…These results agree with the findings of Lu and Zhu (2006) , who reported that TRIA increased the activities of peroxidase (POD) in Glycine max under water stress. More recent studies also suggest that TRIA plays an important role in antioxidant protection under conditions of water stress ( Thind, 1991 ) and salt stress ( Çavuşoğlu et al, 2008 ; Perveen et al, 2011 ). TRIA is believed to play a significant role in inhibiting the lipid peroxidation of biological membranes by acting as an antioxidant compound ( Khan et al, 2009 ).…”
Section: Discussionmentioning
confidence: 99%
“…Root performance in acquiring water and nutrients is determined by the anatomy of the root, such as the size and number of xylem vessels, root cortex width, root hairs number, and suberin formation in the root (Acosta-Motos et al, 2017). Roots anatomy of many species have been reported to change by salinity, including orange (Mohammad, Shiraishi, & Ono, 1999), wheat (Akram, Akhtar, Javed, Wahid, & Rasul, 2002), radish (Çavuşğolu, Kılıç, & Kabar, 2008), lentil (Panuccio, Logoteta, De Lorenzo, & Muscolo, 2011), and finger millet (Krishnamurthy et al, 2014). The changes in root anatomy under salinity might determine the salinity tolerance level of the plant.…”
Section: Introductionmentioning
confidence: 99%